Characterisation of the metabolite profile and microbial community of repeated batch and coculture-fermented greengage wine. (October 2021) - Liu, Jian; Liu, Miao; Ye, Pian; He, Cheng; Liu, Yingjie; Zhang, Suyi; Huang, Jun; Zhou, Jun; Zhou, Rongqing; Cai, Liang
Graphical abstract: Highlights: Total acid content decreased significantly while esters increased with batches. The ketone and terpene contents of first batch was enhanced by coculturing. Volatiles were closely related to functional microbes in various fermentations modes. Key volatiles were major lied on the microbial community and their metabolism. Abstract: This study aimed to investigate the effect of repeated batch fermentation of cocultured Saccharomyces bayanus Y4 and Torulaspora delbrueckii Y7 on the quality of greengage wine. The acidity, as well as citric acid and L-malic acid content, decreased significantly with the batches. The citric acid content of the single culture in each batch was 58.59, 26.27, and 8.45 g/L, respectively. Additionally, the ester content increased with the batches. The respective values were 1627.93, 2249.46, and 2491.17 μg/L for the prophase of coculture. However, volatile content in the fresh wine of Y4 yeast in each batch was high. Ketone and terpene contents in the first batch of coculture significantly increased from 31.64 to 95.60 μg/L and 58.58–95.13 μg/L, respectively. Furthermore, a significant difference was observed between the microbial communities fermented using single culture and coculture. The change in fungal community diversity for coculture pattern was higher than that in the mash-inoculated single strain, which decreased the abundance of dominant fungi. Pichia, Stropharia, Suillus, Malassezia, Trichoderma, Faecalibacterium, and Butyricicoccus were associated with esters, terpenes, phenylethyl alcohol, and β-ionone. Our study provides a new avenue to improve the flavour and quality of wine brewed using a characteristic fruit.